Inarijärven kalatalouden kehittämisen monitavoitearviointi - Rytkönen, Anne-Mari; Marttunen, Mika; Niva, Teuvo; Salonen, Erno; Ahonen, Markku; Paananen, Hannu; Puro-Tahvanainen, Annukka; Leskinen, Jari; Koivisto, Kare; Rauhala, Timo; Heinimaa, Petri
2015